Impact of Gas Flaring on the Environment of Some Communities in Agbarha, Ughelli North Local Government Area, Delta State, Nigeria - Otache, Monday Abel; Godwin, Agbajor Kparobo; Inalegwu, Ocheje Innocent; Oghenekome, Odibo Ewomazino (Journal of Advanced Research in Petroleum Technology & Management; Vol 6 No 1&2 (2020): Journal of Advanced Research in Petroleum Technology and Management, 2021)
Oil production activities are detrimental to man and the immediate environment through gas flaring, thereby releasing greenhouse gases which cause global warming or climate change. This paper is focused on the application of some physical and chemical parameters to assess the level of impacts on environment exposed to gas flaring. Three communities located around the gas flaring activities were selected for this study; Gana and Owevwe with Agbarha-Otor considered as control with no gas flaring activity. Emphasis on soil and water forms the focal point of the research findings at the different collection of 0.5 km, 1 km and 2 km. The collected soil and water samples were used to investigate the pH, Electrical conductivity, Electrical potential, Cation Exchange Capacity, Exchangeable Acidity and the presence of heavy metals. The results showed that the pH of soil and water samples collected at the selected distances from flare points were generally acidic, indicating the presence of acid rain and acid soils around the flare locations. Results also showed that gas flaring activities have an impact on heavy metal concentration in soil of the study area. The results showed higher concentration at test distances near the flare point and lower values at distances further away from flare point. Based on these findings, it was observed that at distance below 1 km, human activities could take place but with caution due to high air temperature, resulting in poor soil water holding capacity on account of low organic matter, water acidity and the presence of heavy metals. How to cite this article:  Abel OM, Godwin AK, Inalegwu OI et al. Impact of Gas Flaring on the Environment of Some Communities in Agbarha, Ughelli North Local Government Area, Delta State, Nigeria. J Adv Res Petrol Tech Mgmt 2020; 6(1&2): 15-21.